Design and Build a New Student Satisfaction Analysis Application Using the Importance Performance Analysis Method at the Universitas Dinamika - Ryan Ivanaldo Wirasandi; Sulistio wati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Dinamika University (Undika) is one of the private universities in East Java which has two (2) faculties and nine (9) study programs, namely: 1) the Faculty of Economics and Business has three (3) study programs, namely, S1 Accounting, S1 Management, and DIII Office Administration; 2) The Faculty of Technology and Information Technology has six (6) study programs, namely, S1 Information Systems, S1 Product Design, S1 Visual Communication Design, S1 Computer Engineering, DIV Film and Television Production, DIII Information Systems. Based on the existing problem, applicants as part of marketing so far have never collected data on the expectations of new students at Undika as part of an evaluation of service improvement at Undika. The impact that occurs is that the Penmaru section has difficulty evaluating the quality of services that need to be improved. Thus, Penmaru can market out with services inside Undika if students are satisfied. The next problem is that there is no comparison of expectations and perceptions of new students. The impact that occurs is the difficulty in comparison, because the comparison can serve as a comparison of how well the services provided and will determine the priority of services that you want to improve in certain parts through analysis. In fact, every improvement in service quality will increase customer satisfaction. Based on the above problems, Penmaru needs an application for analysis of new student satisfaction using Importance Performance Analysis. Based on this, an application is made that can generate analysis based on questionnaire data processing. The results of the analysis can be used to assess the quality of service based on the results of a comparison of the perceptions (expectations) of new students on the real service obtained with the expected service. The quality of service in this study uses Parasuraman theory with five dimensions, namely: Tangible, Reliable, Responsiveness, Assurance, Empathy.